Impact Evaluation of Trade Interventions Paving the Way - Cadot, Olivier (The World Bank, 2011)
The focus of trade policy has shifted in recent years from economy-wide reductions in tariffs and trade restrictions toward targeted interventions to facilitate trade and promote exports. Most of these latter interventions are based on the new mantra of "aid-for-trade" rather than on hard evidence on what works and what does not. On the one hand, rigorous impact-evaluation is needed to justify these interventions and to improve their design. On the other hand, rigorous evaluation is feasible because unlike traditional trade policy, these interventions tend to be targeted and so it is possible to construct treatment and control groups. When interventions are not targeted, such as in the case of customs reforms, some techniques, such as randomized control trials, may not be feasible but meaningful evaluation may still be possible. Theis paper discusses examples of impact evaluations using a range of methods (experimental and non-experimental), highlighting the particular issues and caveats arising in a trade context, and the valuable lessons that are already being learned. The authors argue that systematically building impact evaluation into trade projects could lead to better policy design and a more credible case for "aid-for-trade